Development of visible light active sodium tantalate photocatalyst for hydrogen generation - Pushkar Kanhere (2012)
Generation of hydrogen from water by using a photocatalyst and solar light is a clean and sustainable way to harvest energy. However the photocatalysts developed so far have limited efficiencies under visible radiation, due to lack of suitable photophysical properties. Band engineering of wide band gap photocatalysts is a promising approach to develop highly efficient, visible light driven materials. NaTaO3 is one of the most efficient photocatalysts for the water splitting reaction under Ultra-Violet (UV) radiation. NaTaO3 has large overpotentials and thus allows sufficient space for the modification of the band structure. Therefore, the objective of this project is to develop the visible light sensitive sodium tantalate based photocatalysts with suitable band edge potentials and band gaps. This work includes Density Functional Theory (DFT) based quantum chemical calculations on NaTaO3 materials as well as synthesis, characterization and photocatalytic testing of the selected compounds. Firstly, using computation within the framework of DFT, the band structures of various doped NaTaO3 systems were studied. The analysis of these results was carried out to identify the suitable dopants that would reduce the effective band gap of NaTaO3 and enable the visible light absorption. Among the various candidates, Bismuth and Iron were selected as dopants. Experimental investigations were carried out on Bi doped NaTaO3 and Fe and La-Fe co-doped NaTaO3 powders. It was shown that in the case of Bi doping, the optical and photocatalytic properties of the powders can be changed significantly by tuning the synthesis conditions in the solid state synthesis. Bi doped NaTaO3 powders prepared under mildly Na-rich conditions showed intense visible light absorption extending up to 550 nm. The samples prepared under these conditions were active photocatalysts for Methylene Blue (MB) degradation and showed better performance than the commercially available catalysts (Degussa-P25) under the visible radiation (λ > 420 nm). These samples were also active for hydrogen evolution in presence of sacrificial agent under λ > 390 nm. The optimum conditions for hydrogen evolution (Bi content and amount of co-catalyst loading) were determined by controlled experiments carried out on series of samples. It was revealed that mildly Na-rich conditions led to approximately equal site occupancies of Bi ions at Na and Ta sites. Such occupancies result in the maximum band gap narrowing on account of Bi 6s induced mid-gap energy states as compared to the separate occupancies of Bi ions at Na and Ta site. Occupancy of Bi ions also maintains the ionic charge balance which is beneficial for the photocatalytic reactions. Bi doped NaTaO3 powders were also prepared by low temperature hydrothermal method. These samples offered an advantage of larger surface area, however showed limited visible light absorption (up to 450 nm). Unlike the solid state synthesis, low temperature hydrothermal synthesis did not offer a control over site occupancies of Bi ions in the lattice. Nevertheless, the samples were active for hydrogen evolution under the visible radiation (λ > 390 nm) and the results were comparable with that of the solid state counterparts. Visible light active Fe doped NaTaO3, and La-Fe co-doped NaTaO3 powders were prepared by the solid state route. Fe doped samples did not yield significant amount of hydrogen under the visible radiation which was attributed to the point defects in the lattice. On the other hand, La-Fe co-doped samples showed a maximum hydrogen evolution rate of 0.81 µ•moles•h-1•g-1 upon 0.05% Pt loading under the visible light radiation (λ > 390 nm). The structural characterization and detailed DFT calculations were carried out to understand the role of each dopant in the lattice. It was revealed that Fe ions enable the visible light response, while La ions maintain the ionic charge balance in the lattice and creates characteristic surface nanosteps in co-doped NaTaO3. In conclusion, detailed computational studies were carried on NaTaO3 which serve as a guide to develop visible light active photocatalysts in the future. Novel photocatalysts viz. Bi doped NaTaO3 and La-Fe co-doped NaTaO3 were developed which are active to the photocatalytic hydrogen evolution under the visible radiation. The correlation between the synthesis conditions, crystal structure and photocatalytic activities was established by the experimental characterization of the samples as well as detailed electronic structure calculations. In both the photocatalysts, it was found that along with the appropriate band structure, maintaining the ionic change balance in NaTaO3 lattice is critically important to achieve visible light photocatalytic activity. This study opens a new venue to develop NaTaO3 based compounds. It also demonstrates the viability of using computation to design and select visible light active semiconductor photocatalysts.